Evaluation of Cystic Fibrosis Newborn Screening and Follow-Up Process in Georgia (2022–2023) - Nino Vardosanidze; Nani Kavlashvili; Lali Margvelashvili; Oleg Kvlividze; Mikheil Diakonidze; Saba Iordanishvili; Dodo Agladze (International Journal of Neonatal Screening)
Cystic fibrosis (CF) is a chronic, autosomal-recessive disorder caused by mutations in the CFTR gene, leading to thickened secretions that affect multiple organ systems. This study examines the effectiveness of Georgia’s national CF screening program, which was initiated in 2012 and includes the measurement of immunoreactive trypsinogen (IRT) levels at birth. An analysis of data from 2022 and 2023 revealed a decrease in follow-up attendance for sweat chloride testing among newborns with elevated IRT levels, from 59.9% to 51.2%. The birth prevalence of cystic fibrosis in Georgia varied, suggesting a need to improve both the accessibility of free testing and the quality of follow-up care. Identified barriers include limited access to screening results for pediatricians and the cost of follow-up tests. Recommendations include incorporating free sweat chloride and genetic testing into the national program, as well as improving community education and coordination with social agencies. The identification of 29 CFTR mutations in patients underscores the importance of continued genetic counseling. Overall, while the screening program shows promise, addressing these barriers is essential to improve outcomes and ensure the timely diagnosis and management of cystic fibrosis in Georgia.